Freshwater snails: distributional patterns in selected locales along the Chenab river in Gujranwala Division, Punjab, Pakistan (Zoo Botanica, 2025)
A biological interaction of malacological study was carried out from November 2017 to February 2018 to investigate the distribution and diversity of freshwater snails from four sites along the Chenab River: Head Marala, Wazirabad, Shahbaz Pur, and Rasool Pur. The hand-picking and hand-scoop methods were applied to collect samples of freshwater snails every two weeks. Collected samples of freshwater snails were washed with potable water. The identification of freshwater snails was accomplished by using literature and taxonomic keys. To identify the specimens, the morphometric analysis of the shells was determined using a digital Vernier Caliper. Melanoides tuberculata (Müller, 1774), Viviparus georgianus (Lea, 1834), Viviparus ater (De Cristofori & Jan, 1832) and Bithynia forcarti (Glöer & Pešić, 2012) were identified as members of class Gastropoda (Phylum Mollusca). The prevalence rate of Viviparus georgianus was found in abundance (64.3 %) followed by Bithynia forcarti (16.9 %), Viviparus ater (12.7 %), and Melanoides tuberculata (6.1 %). Simpson species Dominance (1-D: 0.5376), Simpson’s Dominance Index (H: 1.106), and Evenness (0.6906) showed that the four species recorded from the study area were well distributed throughout the study area. This study emphasized exploring the freshwater snails and their diversity along the belt of the river Chenab through selected locales.
Keywords: Freshwater; snails; Chenab river; Head Marala; biodiversity